STRUCTURAL AND FUNCTIONAL MITOCHONDRIAL CHANGES IN CHRONIC HEART FAILURE - Mamedova G.T (TADQIQOTLAR, 2025)
Abstract Chronic heart failure remains one of the most severe cardiovascular syndromes associated with high morbidity and mortality worldwide. Increasing evidence indicates that mitochondrial dysfunction plays a central role in the progression of heart failure by disrupting energy production, redox balance, and calcium homeostasis in cardiomyocytes. Impaired mitochondrial dynamics, including altered fusion, fission, and mitophagy, lead to the accumulation of damaged organelles and progressive cellular injury. Structural and functional mitochondrial alterations are closely associated with myocardial remodeling, fibrosis, and contractile dysfunction. This review summarizes current data on the role of mitochondrial dysfunction in chronic heart failure, highlighting its contribution to disease progression and its potential as a therapeutic target for restoring myocardial energy homeostasis.